College Students’ Use and Reception of Accounting Textbooks: An Indonesian Perspective - Irsyadillah Irsyadillah; Raihani Raihani (Jurnal Dinamika Akuntansi dan Bisnis, 2020)
Due to the limitations of accounting textbooks, students do not realize a broader potential of accounting can make to society outside a scorekeeping practice ascribing priority to shareholders. The purpose of this study is to explore how students in Indonesia use the recommended introductory financial accounting (IFA) textbook to understand whether they use it in a way that allows a more nuanced, contextual and broad-based understanding of accounting. Drawing on the results of four focus groups conducted with students who represent four accounting degrees of Indonesian universities, the study reveals that students are strongly attached to the recommended textbook. It seemed they could not get away from having to use the text if they were to succeed in the course. Therefore, the intellectual source of these students was solely the neoclassical economic paradigm, the primary emphasis of which is satisfying the materialist desires of shareholders. This was evident in the perspectives of both students of conventional and Islamic accounting programs.